Transform techniques based image watermarking : authentication, restoration and copyright protection - Zhu, Xunzhan (2008)
Copyright protection and authentication of digital multimedia contents are increasingly becoming more and more important in parallel with the tremendous development of the Internet. To counter this growing information security problem of illegal distribution and counterfeiting, much research effort has been invested in digitalwatermarking since the last decade. Compared to the traditional methods of protecting digital content ,e.g., cryptography and digital signature, digital watermarking possesses distinct advantages in that it places information directly into the content, which is imperceptible and can neither be removed nor decoded without the required secretkey. In this thesis, novel digitalwatermarking schemes have been proposed by incorporating a widespectrum of transform methods ranging from orthogonal transforms to sampling theory in approximation subspaces, shedding light on some important applications of the watermarking techniques.